Comparison of Molecular, Clinicopathological, and Pedigree Differences Between Lynch-Like and Lynch Syndromes - Xu, Yun; Huang, Zonghao; Li, Cong; Zhu, Congcong; Zhang, Yuqin; Guo, Tian’an; Liu, Fangqi; Xu, Ye (Frontiers in Genetics, 2020)
In this study, we compared the molecular, clinical, and pathological characteristics, as well as pedigrees, between patients with Lynch-like syndrome (LLS) and confirmed Lynch syndrome (LS) to develop appropriate management strategies for patients with LLS and their affected family members. Between June 2008 and September 2018, 81 patients with LLS and 47 patients with LS who developed colorectal cancer (CRC) were enrolled in this study. Multigene panel testing included 139 genes and was performed for all patients. The variants identified in each group were described, and clinicopathological characteristics and pedigrees were compared between the two groups. In the LLS group, a total of 52 variants were detected in 44 (54.3%) patients. Among the 52 variants, 17 were variants of unknown significance in mismatch repair genes, and the other most frequently mutated genes were MUYTH, POLE, BRCA2, and GJB2. The proportion of early-onset patients was significantly higher among the LS probands than among the LLS probands (74.5% and 53.1%, respectively; χ2 = 5.712, P = 0.017). On the other hand, the proportion of primary CRC developed in the rectum was higher in the LLS group than in the LS group (25.9% and 10.6%, respectively; χ2 = 2.358, P = 0.046). There were no significant differences in the occurrence of metachronous CRC (P = 0.632) and extra-CRC (P = 0.145) between the two groups. However, analysis of pedigrees showed that more patients developed CRC in the LS families (P = 0.013), whereas more patients with extra-CRC were observed in the LLS families (P = 0.045). A higher prevalence of male patients was observed in the LLS families (P = 0.036). In conclusion, LLS should be classified as a mixed entity, containing cases of true LS, other hereditary cancer syndromes, and sporadic CRC. The high risks of CRC and extra-CRC, found in our study, suggest that aggressive surgical management should be performed for LLS probands. In addition, we recommend a stringent surveillance protocol that should involve regular follow-ups of the intestine and other organs for probands and affected family members.